If it's not what You are looking for type in the equation solver your own equation and let us solve it.
41(52+13)=x+10-17
We simplify the equation to the form, which is simple to understand
41(52+13)=x+10-17
Simplifying terms in parentheses
41*(+65)=x+10-17
Reorder the terms in parentheses
+(+2665)=x+10-17
Remove unnecessary parentheses
+2665=+x+10-17
We move all terms containing x to the left and all other terms to the right.
-1x=+10-17-2665
We simplify left and right side of the equation.
-1x=-2672
We divide both sides of the equation by -01 to get x.
x=2672
| -5x^3+20x^2+20x+80=0 | | 91n^1+49n=0 | | 63n^2+63n=0 | | 15(x-4)=-6-9 | | -7x+4(3-5)=0 | | 10+x-.33333333x=0 | | 10+x-.33333333=0 | | x^2-15x+10=0 | | 5=2.5-4x | | x^6+8x^3+7=0 | | -1.5x=5 | | (3x+7)*(-8x-7)= | | 2.5-4x=5 | | .4+4x=5 | | 3k+13=19k-8 | | x-9y=19 | | ax-bc=a | | 12+2x-19=x+3 | | 5=0.4-4x | | 5=.5-4x | | 56v^2-23v=63 | | x+2-8=32 | | x+19+2x+27=10 | | (2w-4)/3=w-3 | | X+(X-35)+(X-46)+0.5=360 | | 140x+68=789 | | (X-5)+X+65=180 | | x+19+2x+27=x+6 | | 7+6n=-5 | | 6(x-6)+6=8x-10 | | 7y^3=2x^3+5 | | 10+x-0.33333333x=0 |